ANALISIS PENERAPAN STRATEGI SOCIAL MEDIA MARKETING (SMM) PADA UMKM MIE AYAM & BAKSO MAS DEN TANGERANG SELATAN - Aisyiyah, Aldinenur; Aprilia, Finki; Amalia, Della; Rahmah, Putri Aulia; Karomah, Nurul Giswi (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the implementation of Social Media Marketing (SMM) strategies in the micro, small, and medium enterprise (MSME) Mie Ayam & Bakso Mas Den in South Tangerang. Social Media Marketing has become one of the important strategies for MSMEs to increase visibility, interaction with customers, and product sales in the digital era. This research uses a qualitative descriptive method with a case study approach, where data were obtained through interviews and observations with the MSME owner, observation of social media activities, and documentation of promotional content. The analysis was conducted to evaluate the SMM strategy activities implemented, including types of content, posting frequency, interaction with consumers, and its impact on sales. Based on the SWOT analysis, the results show that Mie Ayam & Bakso Mas Den has actively utilized social media platforms such as Instagram and TikTok, with engaging content strategies and responsive promotions, which have had a positive impact on increasing the number of customers and sales. However, there are opportunities for further development, such as optimizing the use of influencers on social media. This study is expected to provide practical contributions for other MSMEs in implementing Social Media Marketing strategies effectively.